Clinical Value of Machine Learning-Based Ultrasomics in Preoperative Differentiation Between Hepatocellular Carcinoma and Intrahepatic Cholangiocarcinoma: A Multicenter Study - Ren, Shanshan; Li, Qian; Liu, Shunhua; Qi, Qinghua; Duan, Shaobo; Mao, Bing; Li, Xin; Wu, Yuejin; Zhang, Lianzhong (Frontiers in Oncology, 2021)
Abstract Objective: To explore the clinical value of machine learning-based ultrasomics in the preoperative noninvasive differentiation between hepatocellular carcinoma (HCC) and intrahepatic cholangiocarcinoma (ICC). Methods: The clinical data and ultrasonic images of 226 patients from three hospitals were retrospectively collected and divided into training set (n=149), test set (n=38) and independent validation set (n=39). Manual segmentation of tumor lesion was performed with ITK-SNAP, the ultrasomics features were extracted by the Pyradiomics, and ultrasomics signatures were generated using variance filtering and lasso regression. The prediction models for preoperative differentiation between HCC and ICC were established by using support vector machine (SVM). The performance of the three models was evaluated by the area under curve (AUC), sensitivity, specificity and accuracy. Results: The ultrasomics signatures extracted from the grayscale ultrasound images could successfully differentiate between HCC and ICC (p < 0.05). The combined model had a better performance than either the clinical model or the ultrasomics model. In addition to stability, the combined model also had a stronger generalization ability (p < 0.05). The AUC (along with 95% CI), sensitivity, specificity and accuracy of the combined model on the test set and the independent validation set were 0.936 (0.806 - 0.989), 0.900, 0.857, 0.868 and 0.874 (0.733 - 0.961), 0.889, 0.867, 0.872, respectively. Conclusion: The ultrasomics signatures could facilitate the preoperative noninvasive differentiation between HCC and ICC. The combined model integrating ultrasomics signatures and clinical features had a higher clinical value and a stronger generalization ability.